An Endoplasmic Reticulum Cyclophilin Cpr5p Rescues Z-type α1-Antitrypsin from Retarded Folding - CHAN-HUN JUNG; Jeong Hun Lim; 이경희; 임하나 (Bulletin of the Korean Chemical Society, 2014)
Human α1-antitrypsin (α1-AT) is a natural inhibitor of neutrophil elastases and has several dozens of genetic variants. Most of the deficient genetic variants of human α1-AT are unstable and cause pulmonary emphysema. However, the most clinically significant variant, Z-type α1-AT, exhibits retarded protein folding that leads to accumulation of folding intermediates. These aggregate within the endoplasmic reticulum (ER) of hepatocytes, subsequently causing liver cirrhosis as well as emphysema. Here, we studied the role of an ER folding assistant protein Cpr5p on Z-type α1-AT folding. Cpr5p was induced > 2-fold in Z-type α1-AT-expressing yeast cells compared with the wild type. Knockout of CPR5 exacerbated cytotoxicity of Z-type α1-AT, and re-introduction of CPR5 rescued the knockout cells from aggravated cytotoxicity caused by the α1-AT variant. Furthermore, Cpr5p co-immunoprecipitated with Z-type α1-AT and facilitated its protein folding. Our results suggest that protein-folding diseases may be suppressed by folding assistant proteins at the site of causal protein biosynthesis. KCI Citation Count: 1